Analysis of optimized turning parameters of Hastelloy C-276 using PVD coated carbide inserts in CNC lathe under dry condition. (2021) - Modi, Vinayak A.; Kumar, Prashant; Malik, Rohit; Singh Yadav, Anil; Pandey, Anish
Abstract: The major problem regarding machining of nickel-based superalloy such as Hastelloy C-276 is high tool wear for prolonged operation due to work hardening effect and the surface roughness which directly affects the performance of machined component during its application. In this study, the Design of Experiments (DOE) has been used to study the effect of main turning parameters (Cutting speed (V), Feed rate (F) and Depth of Cut (D)) to obtain minimum Cutting force (Fz), Surface Roughness (Ra) and tool wear of carbide inserts with the turning of Hastelloy C-276 under different cutting conditions. Dry machining of the workpiece was performed, and tests were designed according to Taguchi Analysis L16 orthogonal array. ANOVA analysis was performed to determine the importance of machining parameters on Fz, Ra, Tool wear. The results were analysed using Mean plots, signal -to -noise S/N ratio and 3D surface graphs. Optimal operating parameters were determined using the S/N ratio and desirability function analysis. Mathematical models were created for Fz, Ra and tool wear using Response Surface Methodology (RSM). The results indicate that Fz is significantly dependent on V, F and D and is minimum for higher cutting speed and lower feed and depth of cut. Ra is significantly dependent on feed rate and increases with increasing feed rate. Tool wear is significantly dependent on Cutting speed and has a parabolic variation with the same. The composite desirability of the output parameters is acceptable and tool life study is done for the optimized parameters. Chip morphology study and Tool life study was done to understand the nature of chip formed and the deformation of cutting insert.